2009
DOI: 10.1016/j.rmed.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, functional and biochemical changes during recovery from COPD exacerbations

Abstract: The pathways underlying chronic obstructive pulmonary disease exacerbations (ECOPD) remain unclear. This study describes the clinical, functional and biochemical changes during recovery from ECOPD. Thirty hospitalized patients with Anthonisen's type-I ECOPD were evaluated on days 0 (admission), 3, 10 and 40. A five-symptom score (TSS), performance status and quality of life were evaluated. Post-bronchodilator spirometry, blood gases, oxidative stress, C-reactive protein (CRP), serum amyloid-A (SAA), tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 31 publications
(29 reference statements)
3
45
1
10
Order By: Relevance
“…In a previous study from our group, the measurement of several serum biomarkers, including CRP, serum amyloid-A, tumour necrosis factor-a, interleukin-6 and fibrinogen, failed to identify patients with early or late recovery from hospitalisation for AECOPD [23]. In a Swiss study, STOLZ et al [24] showed that plasma pro-adrenomedullin and pro-endothelin levels were associated with the length of hospitalisation, but only pro-adrenomedullin is a predictor of long-term survival.…”
Section: Discussionmentioning
confidence: 78%
“…In a previous study from our group, the measurement of several serum biomarkers, including CRP, serum amyloid-A, tumour necrosis factor-a, interleukin-6 and fibrinogen, failed to identify patients with early or late recovery from hospitalisation for AECOPD [23]. In a Swiss study, STOLZ et al [24] showed that plasma pro-adrenomedullin and pro-endothelin levels were associated with the length of hospitalisation, but only pro-adrenomedullin is a predictor of long-term survival.…”
Section: Discussionmentioning
confidence: 78%
“…В проспективных исследованиях была показана тесная корреляционная связь длительности госпита лизации и сывороточного уровня копептина [11], про адреномедуллина [24], проэндотелина 1 [24], альбу мина [25], тропонина Т [26] и натрийуретического пептида [27]. В одном из исследований оценивались несколько биомаркеров (в т. ч. сывороточные марке ры окислительного стресса, СРБ, сывороточный амилоид А, TNF α, IL 6 и фибриноген) в отношении возможности выявления пациентов с меньшей про должительностью госпитализации, однако, несмотря на длительно присутствовавшие изменения в уров нях этих биомаркеров, ни один из них не явился предиктором снижения проявлений симптомов в ранние сроки [12]. При изучении выраженности симптомов обострения ХОБЛ, темпа их обратного развития и частоты рецидивов показано, что пациен ты, у которых выраженность симптомов не достигла исходного уровня к 35 му дню, наблюдалось стойкое повышение уровня СРБ в сыворотке крови [28].…”
Section: обзорыunclassified
“…Некоторые биомаркеры, такие как СРБ и про кальцитонин, которые определялись в начале госпи тализации по поводу обострения ХОБЛ, не являлись предикторами летального исхода в ближайшем пери оде [11,12], а в противоположность этому, повышен ные уровни копептина были связаны с высоким рис ком смерти во время пребывания в стационаре [11].…”
Section: обзорыunclassified
See 1 more Smart Citation
“…TNF-α is an important cytokine in COPD and is increased in persons with COPD (Karadag, Kirdar, Karul, & Ceylan, 2008;Koutsokera et al, 2009). TNF-α controls cellular migration and permeability and is important in the secretion of several cytokines.…”
Section: Inflammation and Copdmentioning
confidence: 99%